2013
DOI: 10.4103/1119-3077.116911
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided percutaneous transthoracic lung biopsy: First experience in Ibadan, Nigeria

Abstract: Percutaneous lung biopsy had been described in the nineteenth century by Leyden, but image- guided needle chest biopsy only gained widespread acceptance in the 1970s. Currently, tissue sampling of a thoracic lesion is indicated when the diagnosis cannot be obtained by the non-invasive techniques and cytological diagnosis will modify the stage of the disease or influence the therapeutic strategy. Cytology obtained by small-gauge needle aspiration biopsy confirms the nature of the lesion in 80 - 95% of cases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Our institution uses the 3 slice biopsy mode, minimising the procedure time and thereby reducing the risk of complications through the prolonged procedure time. The majority of the published studies to date are also from centres using the 3 slice biopsy mode, thus our practice is in concordance with other institutions [6,[8][9][10][11][17][18][19][20][21].…”
Section: New Techniques In Ct Guided Lung Biopsysupporting
confidence: 72%
“…Our institution uses the 3 slice biopsy mode, minimising the procedure time and thereby reducing the risk of complications through the prolonged procedure time. The majority of the published studies to date are also from centres using the 3 slice biopsy mode, thus our practice is in concordance with other institutions [6,[8][9][10][11][17][18][19][20][21].…”
Section: New Techniques In Ct Guided Lung Biopsysupporting
confidence: 72%
“…This is consistent with earlier reports by Anas and Muhammad[ 8 ] in 2012 in Kano northern Nigeria, Adekanmi and Osobu[ 10 ] in 2020, and Ogbole et al . [ 9 ] in 2010 both in Ibadan, south-western Nigeria, which also showed a male preponderance of 1.3, 1.3, and 1.6, respectively. This is, however, different from the study by Man et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Previous studies have shown that most CTA studies were predominantly requested for the evaluation of cranial lesions. [ 8 9 ] Adekanmi and Osobu[ 10 ] had reported that most patients had cranial/cerebral CTA, followed by pulmonary artery CTA, and then lower limb CTA. The least requested CTA examinations were hepatic and cardiac CTAs.…”
Section: Introductionmentioning
confidence: 99%
“…The methodology employed in this study is generally similar to that recommended by most authors. [ 2 4 6 7 8 9 11 12 13 14 ] Sensitivity of CT-guided percutaneous transthoracic lung biopsy has been put at 76%–96%. [ 2 13 14 15 ] Bozbaş et al ., in a 10-year experience reported a sensitivity of 87.5% following CT-guided transthoracic lung biopsy and a complication rate of 25.1%.…”
Section: Discussionmentioning
confidence: 99%